A Preliminary Study on the Extrusion Resolution of Pluronic F127 for Bioprinting Thermo-responsive Hydrogel Constructs - Suntornnond, Ratima (2016)
Thermo-responsive hydrogels have gained more attention recently due to their unique characteristic of tunable sol-gel transition when temperature is changed. They have been used for many biomedical applications from drug delivery to fabrication of soft tissue scaffolds via 3D bioprinting. In this paper, the preliminary investigation on bioprinted thermo-responsive hydrogels were conducted in order to find out the correlations between size of nozzle, stage moving speed and gas pressure for achieving optimum printing resolution. The hydrogel that was used in this study was pluronic F127 at 24.5 wt % concentration. Two sizes of nozzle were used (25G and 30G) while stage moving speed (printing speed) and gas pressure were designed to be three levels each. A total of 18 experiments were conducted. The results show that the thinnest continuous line (highest resolution) of hydrogel could be obtained even when a larger nozzle is used. This paper suggests a relationship of the main parameters with the size of nozzle on extrusion based bioprinter, and the results from this study may provide a platform for future correlation studies on extrusion based bioprinting.